Pengaruh Metode Socrates Terhadap Kemampuan Berpikir Historis: Analisis Pada Pembelajaran Sejarah Berbasis Masalah - Aji Saputra, Mochammad Ronaldy (Balai Diklat Keagamaan Surabaya, 2024)
The implementation of the Kurikulum Merdeka makes historical thinking skills one of the process skill elements in achieving history learning. Problem-based learning and the Socrates method have been recognized as effective in developing historical abilities. However, no research has so far directed the application of the Socrates method in problem-based history learning toward students' historical thinking abilities. The purpose of this study was to determine the effect of the Socrates method on students' historical thinking abilities in problem-based history learning. This study used a quasi-experimental design with a pretest-posttest group design. The population of this study was all students of class XI MAN 2 Kota Malang. The research sample was determined using a purposive sampling technique, namely 60 students who were divided into 2 groups, namely the experimental group and the control group. The research instrument used was a historical thinking ability test consisting of 10 multiple-choice questions. Data were analyzed both descriptively and inferentially. The results showed that there was a significant difference in students' historical thinking abilities between the experimental group and the control group. Based on the Wilcoxon non-parametric statistical test with an Asymp. Sig. value. (2-tailed) 0,00 < 0,05, it can be concluded that the application of the Socrates Method significantly influences students' historical thinking skills. This shows that the Socrates method has a positive influence on students' historical thinking skills in problem-based history learning.